Development of PANIPATIK (Batik Theme Place Value Board) Learning Media for Place Value Material - Isania Marsel Viliyati; Mewa Zabeta (Jurnal Inovasi Matematika, 2025)
This study aims to develop PANIPATIK (Batik Themed Place Value Board) learning media that can facilitate learning place value material in fourth grade. The research method applied in this study is Research and Development (R&D) approach. with the ADDIE model, namely: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used include observation, questionnaires, and tests. The results of the study indicated that the PANIPATIK media was classified very valid with a percentage of 93.84% from material experts and 95.00% from media experts. The practicality of the media is also very practical based on the response rate of 89.21% of students. The effectiveness of the media was assessed based on test results after using the PANIPATIK media, where students achieved an average score of 82.08 with a success rate of 83.33%, which falls under the good category. Thus, the PANIPATIK media is valid, effective, and well-received by students, making it suitable as one of the learning media supporting the mathematics learning process on place value material.